Ab Initio Studies of Hydrogen Ion Insertion into β-, R-, and γ-MnO2 Polymorphs and the Implications for Shallow-Cycled Rechargeable Zn/MnO2 Batteries. Issue 14 (14th November 2018) - Vasiliev, Igor; Magar, Birendra Ale; Duay, Jonathon; Lambert, Timothy N.; Chalamala, Babu
Abstract : At a low depth of discharge, the performance of rechargeable alkaline Zn/MnO2 batteries is determined by the concomitant processes of hydrogen ion insertion and electro-reduction in the solid phase of γ-MnO2 . Ab initio computational methods based on density functional theory (DFT) were applied to study the mechanism of hydrogen ion insertion into the pyrolusite (β), ramsdellite (R), and nsutite (γ) MnO2 polymorphs. It was found that hydrogen ion insertion induced significant distortion in the crystal structures of MnO2 polymorphs. Calculations demonstrated that the hydrogen ions inserted into γ-MnO2 initially occupied the larger 2 × 1 ramsdellite tunnels. The protonated form of γ-MnO2 was found to be stable over the discharge range during which up to two hydrogen ions were inserted into each 2 × 1 tunnel. At the same time, the study showed that the insertion of hydrogen ions into the 1 × 1 pyrolusite tunnels of γ-MnO2 created instability leading to the structural breakdown of γ-MnO2 . The results of this study explain the presence of groutite (α-MnOOH) and the absence of manganite (γ-MnOOH) among the reaction products of partially reduced γ-MnO2 .